Intention to Quit of Proactive Health Workers: The Intervening Role of Employee Engagement and the Moderated Mediating Effect of Job Autonomy - Gadi, Paul Dung; Silas, Gontur; Bagobiri, Esther (International Journal of Business, Management and Economics, 2022)
As a necessary condition for the sustainability and success of teaching hospitals, maintaining proactive health personnel with the ability to be high performers is acknowledged. A few studies have logically clarified and empirically simplified the relationship between proactive employees and intention to quit, which signifies an engaged, proactive tendency to establish actual turnover behavior. However, this study target to resolve these research gaps. This paper predicted that the correlation between proactive health workers and intention to quit was likely mediated by employee engagement and job autonomy as a center point mechanism of motivation. Job autonomy (JA) as a significant framework is expected to buffer the link between proactive health employee and employee engagement. The present article developed a moderated mediated model that incorporates these variables. This study was consistent with previous studies carried out on health workers in Nigerian teaching hospitals. The results of this research help to expose the attrition intentions displayed by conscientious health workers.